Urbanisation, urban environmental quality, national socio-economic conditions and diseases burden in Africa: a research agenda for spatio-temporal analyses of subregional characteristics - Ingwe, Richard (Journal for Geography, 2013)
The investigation of socio-economic, political and environmental aspects of urbanization in Africa is gaining research attention. Most recently, information on the patterns in urbanization, population growth, slumisation, among other aspects of urban Africa within the past quarter of a century or thereabout were reported. While this report elucidated on the relevant challenges, it was restricted to the regional patterns of the variables investigated. This report indicates that more information on the sub-regional aspects of these variables is required to elucidate on urban planning in the region and its sub-regions. Here, the ways forward in investigating these issues and variables underlying them are outlined. The theoretical, methodological, spatial and temporal aspects or requirements of the proposed research are discussed to provide a compass for future research.